Experimental Investigation on Metallurgical and Mechanical Properties and Wear Behavior of Al5032/SiC Nanocomposites - S. A. Muhammed Abraar; N. Mohan Rajhu; T. Vishnu Vardhan; Abhishek Agrawal; Kuldeep K. Saxena; V. Savithiri; Dharam Buddhi; K. Senthilvel; B. Ramesh (Materials Research, 2023)
Aluminium metal matrix composites are highly dominated composites for various applications such as military, marine, aircraft, aerospace and automobile because of their corrosion resistance, tribological and mechanical properties. In this research, aluminium alloy 5032 composite reinforced with SiCnp (4, 8, 12 and 16 wt.%) was manufactured using stir casting method and subjected to various mechanical, metallurgical and wear tests. The novelty of this research lies in the fabrication and characterization of Al5032/SiCnp composites, which has been not done before. The Energy Dispersive X ray analysis (EDAX) was used to examine the presence of SiC in Al5032 matrix and Scanning Electron Microscope (SEM) was employed to examine the microstructure of the composite. Further micro hardness, wear resistance, tensile and impact tests were carried out. The aforesaid properties increases upto 12 wt.% addition of silicon carbide in Al5032 alloy and thereafter reduces. The nanocomposite Al5032/12wt.%SiC exhibits 98 HV, 256 MPa tensile strength, 19 MPa impact strength and 5 mg wear loss.